ASSESSMENT OF THE PERSONALITY STRUCTURE OF OPIAD ADDICTS AND PERSONS WITH INTERNET USE DISORDER - Milinović, Milica; Tepsic Ostojic, Vesna (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Internet use disorder is a psychophysical disorder that involves the appearance of tolerance, withdrawal symptoms, affective disturbances and disturbed social relationships. Neurobiological and pharmacological data suggest similarities in the pathopsychology of opiate addiction and pathological gambling. The aim of this research is to compare the sociodemographic characteristics of people with Internet use disorder, people who are addicted to opiates and a control group. As well as to compare psychological characteristics according to the Big Five model and psychopathological characteristics, and determine the degree of their expression in persons belonging to the mentioned groups. The research was conceived as a cross-sectional clinical study based on a methodological approach that includes the application of comparative methodology, with the use of assessment scales and psychological-psychiatric batteries for personality assessment. The total sample includes 300 subjects: 100 subjects with opiate addiction, 100 subjects showing symptoms of Internet use disorder, and 100 subjects of the control group. The results of this research indicate that personality characteristics such as empathy, extroversion, agreeableness, conscientiousness, openness and cooperation are expressed to a lesser extent in people with Internet use disorder and people addicted to opiates, compared to the control group. The obtained results contribute to the classification of Internet use disorders and suggest placing them in the diagnostic category of behavioral addictions.